2014
DOI: 10.1007/s00440-014-0564-x
|View full text |Cite
|
Sign up to set email alerts
|

The parabolic Anderson model in a dynamic random environment: space-time ergodicity for the quenched Lyapunov exponent

Abstract: 35 pages, 4 figures.International audienceWe continue our study of the parabolic Anderson equation $\partial u(x,t)/\partial t = \kappa\Delta u(x,t) + \xi(x,t)u(x,t)$, $x\in\Z^d$, $t\geq 0$, where $\kappa \in [0,\infty)$ is the diffusion constant, $\Delta$ is the discrete Laplacian, and $\xi$ plays the role of a \emph{dynamic random environment} that drives the equation. The initial condition $u(x,0)=u_0(x)$, $x\in\Z^d$, is taken to be non-negative and bounded. The solution of the parabolic Anderson equation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The results of [ErhHolMai14] (see Remark 8.10), interesting as they are on their own, are only the preparation for a much deeper result that is derived in the follow-up paper [ErhHolMai15a]. Here a stronger mixing property (called Gärtner-hyper-mixing) is imposed, under which it is shown that (at least for the localised initial condition u 0 D ı 0 ) lim Ä!1 0 .Ä/ D h .0; 0/i.…”
Section: Remark 811 (Moment-intermittency Versus Almost-sure Intermimentioning
confidence: 85%
“…The results of [ErhHolMai14] (see Remark 8.10), interesting as they are on their own, are only the preparation for a much deeper result that is derived in the follow-up paper [ErhHolMai15a]. Here a stronger mixing property (called Gärtner-hyper-mixing) is imposed, under which it is shown that (at least for the localised initial condition u 0 D ı 0 ) lim Ä!1 0 .Ä/ D h .0; 0/i.…”
Section: Remark 811 (Moment-intermittency Versus Almost-sure Intermimentioning
confidence: 85%
“…The parabolic Anderson model (PAM) has been extensively studied both when the potential ξ(t, x) is a real-valued field (see e.g. [7,8,13] and the references therein) and when it is a white Gaussian noise which is a distributional-valued field (see e.g. [2,1] and their cited references).…”
Section: Introductionmentioning
confidence: 99%